Knowledge, Attitude and Practices of Women Towards Breast Cancer in Arbaji Village, Gezira State, Sudan (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Internal Medicine; Research